Child Health Clinical Outcome Review Programme: Health Care Utilisation, Care Pathways and Educational Status in Children and Young People with Adolescent Mental Health problems with a focus on Self harm, Eating Disorders and Anxiety and Depression - Sophie Wood; Ann John; Alison Kemp; Bethan Carter; Melissa Wright (International Journal of Population Data Science, 2017)
ABSTRACT